A new representational ecosystem for design teaching in the studio. (November 2016) - Dorta, Tomás; Kinayoglu, Gôkçe; Boudhraâ, Sana
Abstract : Simulation tools available in a design studio can be named Representational Ecosystem. It exists a variety, balance, exchange and interoperability amongst the elements of this ecosystem. Due to the monolithic approach introduced by generic 3D modelling software, which neither considers the multiplicity of representations nor facilitates abstraction, the current 'digital' paradigm fails to effectively support the co-design process in design teaching in the studio. This paper presents a case study that analyses the utilization of an immersive co-design environment called Interconnected Hybrid Ideation Space, amongst other kind of representations, during an undergraduate design studio. The epistemology and principles of this new representational paradigm for teaching the design studio are described: being bilaterally-hybrid, supporting multiple representations and scales, and fostering co-design. Highlights: Formulation of the principles for a new representational ecosystem. The epistemology and principles of the new paradigm. Updating Lebahar's Graphical Simulation System to reflect current design practice. Analyse the interconnected HIS as a binding component of the representation environment. The pedagogical implications of a such representational ecosystem in teaching the design studio.